2014
DOI: 10.1145/2641568
|View full text |Cite
|
Sign up to set email alerts
|

Can I Recognize My Body's Weight? The Influence of Shape and Texture on the Perception of Self

Abstract: The goal of this research was to investigate women's sensitivity to changes in their perceived weight by altering the body mass index (BMI) of the participants' personalized avatars displayed on a large-screen immersive display. We created the personalized avatars with a full-body 3D scanner that records the participants' body geometry and texture. We altered the weight of the personalized avatars to produce changes in BMI while keeping height, arm length, and inseam fixed and exploited the correlation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 35 publications
2
59
0
1
Order By: Relevance
“…New emerging technologies allow for 3D fullbody scanning so that avatars are matched to a specific user in visual features and body size (Piryankova et al, 2014). Having the flexibility to vary the visual body features of an avatar in realistic ways could address further questions about the role of cognition.…”
Section: Discussionmentioning
confidence: 99%
“…New emerging technologies allow for 3D fullbody scanning so that avatars are matched to a specific user in visual features and body size (Piryankova et al, 2014). Having the flexibility to vary the visual body features of an avatar in realistic ways could address further questions about the role of cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual reality studies have demonstrated that self-avatars with different ages [Hershfield et al 2011], shapes [Piryankova et al 2014], and races [Kilteni et al 2013] alter participants' perception and attitudes. Future work could investigate if self-perception of strength and power can also be influenced by a modified self-avatar.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…A within-subjects design was preferred given the greater variability of body size perception between subjects [22] due to psychological condition, thoughts about ideal body size, media exposure or body dissatisfaction [39]. As in other studies assessing perceived body size [10,27,39] we adopted various strategies to compensate for practice /habituation bias.…”
Section: Methodsmentioning
confidence: 99%
“…Perceived Body Weight: To measure perceived body weight, we used a body visualization tool (bodyvisualizer.com; see Figure 3) adopted by other studies for the same purpose [39]. People adjusted the weight related dimension of the body of a 3D avatar displayed on the screen to correspond to their perceived body size [10,27,39].…”
Section: Multi-measurement Approachmentioning
confidence: 99%
See 1 more Smart Citation